PENGARUH PERBEDAAN KONSENTRASI EKSTRAK BUAH MENGKUDU (MORINDA CITRIFOLIA L.) TERHADAP PERTUMBUHAN TRICHOPHYTON RUBRUM SECARA IN VITRO - Tracy Angelica (2024)
Dermatophytosis is a fungal infection that attacks the epidermis and keratin, with the species causing one of them being Trichophyton rubrum. Long-term use of chemical drugs can potentially cause side effects in the form of toxic effects and resistance. Noni fruit contains flavonoids, alkaloids, tannins, saponins and phenols which are known to inhibit fungal growth. The aim of this research was to determine the effect of different concentrations of noni fruit extract (Morinda citrifolia L.) on the growth of the fungus T. rubrum in vitro. This research was conducted with a laboratory experimental post-test control group. In this test, noni fruit extract was obtained using the 96% ethanol maceration method. Testing for anti-fungal activity was carried out using the well diffusion method with the independent variables, namely noni fruit extract in concentrations of 4%, 6%, 8%, 10% and 12.5% as well as ketoconazole (positive control) and distilled water (negative control). The results of the research showed that there was an inhibitory zone that was produced after being treated with noni fruit extract. Observations were made at 24 hours and 48 hours. The extract concentration with the highest inhibitory power was found at a concentration of 8%, with an average inhibitory zone diameter of 8.095 mm in 48 hours observations. The conclusion of this research is that noni fruit extract in concentrations of 4%, 6%, 8%, 10% and 12.5% is effective in inhibiting the growth of the fungus T. rubrum.